Geological and geochemical evolution of the Trincheira Complex, a Mesoproterozoic ophiolite in the southwestern Amazon craton, Brazil - RIZZOTTO, Gilmar José (2012)
We document the ﬁrst-known Mesoproterozoic ophiolite from the southwestern part of the Amazon craton, corresponding to the Trincheira Complex of Calymmian age, and propose a tectonic model that explains many previously enigmatic features of the Precambrian history of this key craton, and discuss its role in the reconstruction of the Columbia supercontinent. The complex comprises extrusive rocks (ﬁne-grained amphibolites derived from massive and pillowed basalts), maﬁc–ultramaﬁc intrusive rocks, chert, banded iron formation (BIFs), pelites, psammitic and a smaller proportion of calc-silicate rocks. This sequence was deformed, metasomatized and metamorphosed during the development of the Alto Guaporé Belt, a Mesoproterozoic accretionary orogen. The rocks were deformed by a single tectonic event, which included isoclinal folding and metamorphism of the granulite–amphibolite facies. Layered magmatic structures were preserved in areas of low strain, including amygdaloidal and cumulate structures. Metamorphism was pervasive and reached temperatures of 780–853 °C in maﬁc granulites and 680–720 °C in amphibolites under an overall pressure of 6.8 kbar. The geochemical composition of the extrusive and intrusive rocks indicates that all noncumulus maﬁc–ultramaﬁc rocks are tholeiitic basalts. The maﬁc–ultramaﬁc rocks display moderate to strong fractionation of light rare earth elements (LREE), near-ﬂat heavy rare earth element (HREE) patterns and moderate to strong negative high ﬁeld strength element (HFSE) anomalies (especially Nb), a geochemical signature typical of subduction zones. The lowest units of maﬁc granulites and porphyroblastic amphibolites in the Trincheira ophiolite are similar to the modern mid-ocean ridge basalt (MORB), although they locally display small Ta, Ti and Nb negative anomalies, indicating a small subduction inﬂuence. This behavior changes to an island arc tholeiite (IAT) signature in the upper units of ﬁne-grained amphibolites and amphibole rich-amphibolites, characterized by progressive depletion in the incompatible elements and more pronounced negative Ta and Nb anomalies, as well as common Ti|and Zr negative anomalies. Tectono-magmatic variation diagrams and chondrite-normalized REE and primitive mantle normalized patterns suggest a back-arc to intra-oceanic island arc tectonic regime for the eruption of these rocks. Therefore, the Trincheira ophiolite appears to have originated in an intraoceanic supra-subduction setting composed of an arc-back-arc system. Accordingly, the Trincheira Complex is a record of oceanic crust relics obducted during the collision of the Amazon craton and the Paraguá block during the Middle|Mesoproterozoic. Thus, the recognition of the Trincheira ophiolite and suture signiﬁcantly changes views on the evolution of the southern margin of the Amazon craton, and how it can inﬂuence the global tectonics and the reconstruction of the continents